Substantial seagrass blue carbon pools in the southwestern Baltic Sea include relics of terrestrial peatlands - Stevenson, Angela; Ó Corcora, Tadhg C.; Hukriede, Wolfgang; Schubert, Philipp R.; Reusch, Thorsten B. H. (Frontiers in Marine Science, 2023)
Seagrass meadows have a disproportionally high organic carbon (Corg) storage potential within their sediments and thus can play a role in climate change mitigation via their conservation and restoration. However, high spatial heterogeneity is observed in Corg, with wide differences seen globally, regionally, and even locally (within a seagrass meadow). Consequently, it is difficult to determine their contributions to the national remaining carbon dioxide (CO2) budget without introducing a large degree of uncertainty.To address this spatial heterogeneity, we sampled 20 locations across the German Baltic Sea to quantify Corg stocks and sources in Zostera marina seagrass-vegetated and adjacent unvegetated sediments. To predict and integrate the Corg inventory in space, we measured the physical (seawater depth, sediment grain size, current velocity at the seafloor, anthropogenic inputs) and biological (seagrass complexity) environment to determine regional and local drivers of Corg variation.Here we show that seagrass meadows in the Germany constitute a significant Corg stock, storing on average 1,920 g C/m 2 , three times greater than meadows from other parts of the Baltic Sea, and three-fold richer than adjacent unvegetated sediments. Stocks were highly heterogenous; they differed widely between (by 22-fold) and even within (by 1.5 to 31-fold) sites. Regionally, Corg was controlled by seagrass complexity, fine sediment fraction, and seawater depth. Autochthonous material contributed to 12% of the total Corg in seagrassvegetated sediments and the remaining 88% originated from allochthonous sources (phytoplankton and macroalgae). However, relics of terrestrial peatland material, deposited approximately 6,000 years BP during the last deglaciation, was an unexpected and significant source of Corg.Collectively, German seagrasses in the Baltic Sea are preventing 2.01 Mt of future CO2 emissions. Because Corg is dependent on high seagrass complexity, the richness of this pool may be contingent on seagrass habitat health. Disturbance of this Corg stock could act as a source of CO2 emissions. However, the high spatial heterogeneity warrant site-specific investigations to obtain accurate estimates of blue carbon, and a need to consider millennial timescale deposits of Corg beneath seagrass meadows in Germany and potentially other parts of the southwestern Baltic Sea.